Ischemic Retinal Vasculitis Associated with Cataract Surgery and Intracameral Vancomycin - Lucas T. Lenci; Eric K. Chin; Christi Carter; Stephen R. Russell; David R. P. Almeida (Case Reports in Ophthalmological Medicine)
Recently, there have been reports suggesting that intracameral vancomycin has been associated with retinal vasculitis; some have described this phenomenon as postoperative hemorrhagic occlusive retinal vasculitis. We present a case of a 65-year-old woman who underwent uncomplicated phacoemulsification and posterior chamber intraocular lens implantation followed by intracameral antibiotic prophylaxis. Unlike prior reports, this report demonstrates a case of mild visual reduction and minimal inflammation with subtle but complete unilateral peripheral retinal ischemia associated with cataract surgery and intracameral vancomycin, suggesting a spectrum of toxicity that may be underrecognized.